Failure modes and mechanical properties of double-layer rock-like composite specimens with a single fissure under triaxial compression - Xiao, Taoli; Xu, Ke; Lu, Yifan; She, Haicheng (Frontiers in Materials, 2024)
Geotechnical engineering disasters often result from instability failures in layered and heterogeneous fissured rock masses. However, the key mechanisms governing mechanical properties and crack propagation in these rock masses remain unclear. This study presents triaxial compression tests on double-layer rock-like specimens composed of limestone and sandstone materials, containing a single fissure, to investigate the effects of fissure angles and positions on the strength and failure modes of these double-layer specimens under varying confining pressure. The experimental results reveal that the intact composite rock approaches the strength of sandstone but is deformation-limited by limestone. Under constant confining pressure (σ3 = 5MPa), the fissure angle affects initial crack initiation, and fissure position dictates the failure mode and extent, while increased confining pressure induces overall shear failure in the composite rock, with the failure mode being predominantly influenced by confining pressure. Concerning mechanical deformation, augmenting the fissure angle and confining pressure substantially enhances the elasticity and ductility of the composite rock. Regarding volumetric deformation, the extent of volume shrinkage in the composite rock is influenced by both fissure angle and confining pressure, while volume expansion is influenced by fissure position. Under uniaxial compression, fissured composite rock exhibits the most unstable crack propagation, resulting in early failure. Triaxial compression shows that a higher fissure angle stabilizes crack propagation while confining pressure variation affects stability only when the fissure is in limestone. When the fissure is in sandstone, crack propagation stability remains at its highest. Furthermore, an increase in fissure angle, higher confining pressure, and changes in fissure position from sandstone through the contact interface to limestone contribute to an increasing trend in the peak strength and elastic modulus of the composite rock. Fissure-induced rock degradation is primarily influenced by the fissure angle. These findings are significant for guiding engineering construction and design, providing valuable insights to geotechnical engineers, and enhancing safety in rock engineering projects.